Chlorquinaldol inhibits the activation of nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing protein 3 inflammasome and ameliorates imiquimod-induced psoriasis-like dermatitis in mice. (25th September 2022) - Chen, Yanhong; Chen, Xiuhui; Liang, Shuli; Ou, Yitao; Lin, Geng; Hua, Lei; Wu, Xinyi; Zhou, Yinghua; Liu, Zhuorong; Cai, Haowei; Yang, Zhongjin; Hu, Wenhui; et al.
Abstract: Psoriasis is a common chronic autoinflammatory/autoimmune skin disease associated with elevated pro-inflammatory cytokines. The pivotal role of interleukin (IL)-1β and nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing protein 3 (NLRP3) inflammasome in the pathogenesis of psoriasis has been widely described. Accordingly, the suppression of NLRP3-dependent IL-1β release is a potential therapy for psoriasis. Repurposing marketed drugs is a strategy for identifying new inhibitors of NLRP3 inflammasome activation. Herein, chlorquinaldol (CQD), a historic antimicrobial agent used as a topical treatment for skin and vaginal infections, was found to have a distinct effect by inhibiting NLRP3 inflammasome activation at concentrations ranging from 2 to 6 μM. CQD significantly suppressed apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC) oligomerization, NLRP3-ASC interaction, and pyroptosis in macrophages. The levels of cleaved IL-1β and caspase-1 were reduced by CQD in the cell lysates of macrophages, suggesting that CQD acted on upstream of pore formation in the cell membrane. Mechanistically, CQD reduced mitochondrial reactive oxygen species production but did not affect the nuclear factor-κB (NF-κB) pathway. Intraperitoneal administration of CQD (15 mg/kg) for 6 days was found to improve the skin lesions in the imiquimod-induced psoriatic mouse model (male C57BL/6 mice), while secretion of pro-inflammatory cytokines (IL-17 and IL-1β) and keratinocyte proliferation were significantly suppressed by CQD. In conclusion, CQD exerted inhibitory effects on NLRP3 inflammasome activation in macrophages and decreased the severity of psoriatic response in vivo . Such findings indicate that the repurposing of the old drug, CQD, is a potential pharmacological approach for the treatment of psoriasis and other NLRP3-driven diseases. Graphical abstract: Image 1 Highlights: Chlorquinaldol reduces NLRP3 inflammasome activation in vitro . Chlorquinaldol inhibits mitochondrial reactive oxygen species production in vitro . Chlorquinaldol decreases the severity of psoriatic response in vivo .